Phagocytic clearance of presynaptic dystrophies by reactive astrocytes in Alzheimer's disease - Gómez-Arboledas, Ángela; Davila, Jose Carlos; Sánchez-Mejías, Elisabeth; Navarro, Victoria; Núñez-Díaz, Cristina; Sánchez-Varo, Raquel María; Sanchez-Mico, Maria Virtudes; Trujillo-Estrada, Laura Isabel; Fernández-Valenzuela, Juan José; Vizuete, Marisa; Comella, Joan X.; Galea, Elena; et al. (Wiley, 2018)
Reactive astrogliosis, a complex process characterized by cell hypertrophy and upregulation of components of intermediate filaments, is a common feature in brains of Alzheimer's patients. Reactive astrocytes are found in close association with neuritic plaques; however, the precise role of these glial cells in disease pathogenesis is unknown. In this study, using immunohistochemical techniques and light and electron microscopy, we report that plaque-associated reactive astrocytes enwrap, engulf and may digest presynaptic dystrophies in the hippocampus of amyloid precursor protein/presenilin-1 (APP/PS1) mice. Microglia, the brain phagocytic population, was apparently not engaged in this clearance. Phagocytic reactive astrocytes were present in 35% and 67% of amyloid plaques at 6 and 12 months of age, respectively. The proportion of engulfed dystrophic neurites was low, around 7% of total dystrophies around plaques at both ages. This fact, along with the accumulation of dystrophic neurites during disease course, suggests that the efficiency of the astrocyte phagocytic process might be limited or impaired. Reactive astrocytes surrounding and engulfing dystrophic neurites were also detected in the hippocampus of Alzheimer's patients by confocal and ultrastructural analysis. We posit that the phagocytic activity of reactive astrocytes might contribute to clear dysfunctional synapses or synaptic debris, thereby restoring impaired neural circuits and reducing the inflammatory impact of damaged neuronal parts and/or limiting the amyloid pathology. Therefore, potentiation of the phagocytic properties of reactive astrocytes may represent a potential therapy in Alzheimer's disease.
Keywords: Alzheimer, Enfermedad de; Alzheimer's disease; Neurodegeneration; Neuropathology; Reactive astrocyte; Synaptopathy